(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
A zinc dipyrrin complex with a structural and functional design, that mimics the natural photonic antenna of a green plant, has been synthesized and incorporated into new designed model of mesoporous silica. The dye complex is composed of two dipyrromethene ligands which are connected to a central zinc(II) metal ion through the four nitrogen atoms. The dye complex has been characterized using various spectroscopic techniques,1HNMR, IR, and X-ray crystallography to elucidate their structure. UV-vis absorption and fluorescence spectroscopy were used to determine the optical properties of the dye before its encapsulation into the silica framework, and after being trapped in the silica pores. A comparison of the results obtained shows that the silica pores have a significant effect on the fluorescence quantum yield, the excited state lifetime, and the emission of the encapsulated dye molecules.